2b-6=x

Simple and best practice solution for 2b-6=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2b-6=x equation:


Simplifying
2b + -6 = x

Reorder the terms:
-6 + 2b = x

Solving
-6 + 2b = x

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 2b = 6 + x

Combine like terms: -6 + 6 = 0
0 + 2b = 6 + x
2b = 6 + x

Divide each side by '2'.
b = 3 + 0.5x

Simplifying
b = 3 + 0.5x

See similar equations:

| 97=-7(1-7b)+3b | | -4(x+2y)-8(2x-4)= | | 24=-6(4b-7) | | -32-(54)= | | 2x+6+8x-2=64 | | -6+7r=2+6(-8+2r) | | 3v-12=-7(v+6) | | 5y^3+17y^2=12y | | 12x+18=18x | | 3x+4=12-8 | | 7m-5m-6=-2m+6 | | 47-5= | | 3(-4+4n)+7=-89 | | 2x-7=2(x-4) | | 12x+18=28x | | F(2)=x^2+6x+7 | | 2(x-4)+2x=(-6x)-2 | | 5x+6-10= | | y+20=-3 | | 3x+x^2+6=8x | | 8(1-4v)=2v+8 | | -37+8n=-(-2n-5) | | 90=5(-4x-5)-3x | | 3a-2(4a-12)=6a+2 | | H=ab | | n-5-4n=11 | | -8.4+9.6=1.2 | | 5x-14=89 | | 21-9(1-4x)=-24 | | 5x+36=3x+32 | | 4(1w+3)=1w-15 | | 5(4+5n)=-6n+20 |

Equations solver categories